Towards Islamic worldview based corporate governance framework - Htay, Sheila Nu Nu; Adnan, Muhammad Akhyar; Hj. Mohammed Ibrahim, shahul hameed; Ab. Rashid, Hafiz Majdi (2010)
Codes on corporate governance (CG) mainly derive recommendations from the concept of agency theory. The said theory and one of the earliest reports on CG, i.e. Cadbury Report (1992) in UK focused specifically on shareholder oriented nature of governance. Later on, the accountability of directors has been extended to other stakeholders. Therefore, if the trend of the evolution of the corporate governance is observed, shareholder-centred role of the directors has been integrated with responsibilities towards the stakeholders. It can be summarized that the current CG guidelines are a combination of the concepts of stakeholder theory and agency theory. Hence, overall progress of the development of the conventional CG codes has been done with a problem solving approach by tackling emerging problems. However, even with the existence of the guidelines, CG failures still exist. Thus, the effectiveness of the existing codes are questionable since they are not concrete solutions. It might be for the reason that they are man-made guidelines and based on the human reasoning after examining past events and predicting possible future problems. Therefore, it should be concluded that only Islamic worldview based corporate governance framework (IWBCGF) will guide the directors to perpetual solutions of the current and future CG problems.